2021
DOI: 10.2147/ijn.s323831
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends and Challenges in Pharmacoeconomic Aspects of Nanocarriers as Drug Delivery Systems for Cancer Treatment

Abstract: Nanotherapy is a part of nanomedicine that involves nanoparticles as carriers to deliver drugs to target locations. This novel targeting approach has been found to resolve various problems, especially those associated with cancer treatment. In nanotherapy, the carrier plays a crucial role in handling many of the existing challenges, including drug protection before early-stage degradations of active substances, allowing them to reach targeted cells and overcome cell resistance mechanisms. The present review co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 200 publications
(263 reference statements)
1
21
0
Order By: Relevance
“…Moreover, biomedical agents should be effectively eliminated from the body to reduce the level of nanoparticle accumulation in targeted cells, tissues, or organs. Hence, nanocarriers need to be moderately stable to make them more degradable and clearable, resulting in a lower bioaccumulation and a favorable risk–benefit ratio . The stability of QU@UiO-66-R (R = −H, −NH 2 , and −NO 2 ) samples in PBS at pH = 5.0 at 37 °C was investigated (Figures S14–S16 in the SI).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, biomedical agents should be effectively eliminated from the body to reduce the level of nanoparticle accumulation in targeted cells, tissues, or organs. Hence, nanocarriers need to be moderately stable to make them more degradable and clearable, resulting in a lower bioaccumulation and a favorable risk–benefit ratio . The stability of QU@UiO-66-R (R = −H, −NH 2 , and −NO 2 ) samples in PBS at pH = 5.0 at 37 °C was investigated (Figures S14–S16 in the SI).…”
Section: Resultssupporting
confidence: 79%
“…Hence, nanocarriers need to be moderately stable to make them more degradable and clearable, resulting in a lower bioaccumulation and a favorable risk− benefit ratio. 108 The stability of QU@UiO inhibited cell growth in a dose-dependent manner. This obviously revealed that the viability of the cells after 48 h of treatment decreased with increasing concentration (Figure 7).…”
Section: Drug Loading and Release Studymentioning
confidence: 99%
“…Recently, nano-drug formulations have frequently been studied in amalgamation with natural products to minimize the toxicity. Consequently, consuming green nano-formulations for drug delivery systems can increase the therapeutic property and minimize the adverse effects of the drugs ( Milewska et al, 2021 , Tan et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…PEG-coated NPs not only avoid plasma protein adsorption, but also minimize interactions with phagocytes and increase blood circulation time [ 34 , 35 ]. This new specific drug delivery method has greater advantages than traditional intravenous or oral delivery, such as the controlled release of drugs, better targeting ability, improved bioavailability of drugs, and reduced damage to normal tissues [ 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%